U-Pb zircon and Re-Os molybdenite age of the Siah Kamar porphyry molybdenum deposit, NW Iran. Issue 14 (22nd September 2019) - Simmonds, Vartan; Moazzen, Mohssen; Selby, David
ABSTRACT: The Siah Kamar porphyry Mo deposit is the newly discovered deposit of this type in the Neo Tethys-related Urumieh–Dokhtar magmatic arc, northwest Iran. Mineralization occurs as stock-work quartz–molybdenite and mono-mineralic molybdenite veinlets within the porphyry quartz-monzonite stock and the country rocks, accompanied by locally scattered later-stage and cross-cutting quartz-chalcopyrite-pyrite veinlets in the trachy-andesite and trachy-basalt country rocks. U–Pb zircon geochronology of the porphyry stock yielded Early Oligocene dates of 32.7 ± 0.4 to 30.9 ± 0.4 Ma (at 2σ level). The Th/U ratios of the zircons range between 0.48 and 0.77, and they possess initial εHf(t) values of 3.2 to 12.1, which may suggest a dominant mantle source for the magma. Molybdenite separates yielded rhenium contents between ~10 and 41 ppm (average ~26 ppm, n = 4) and slightly younger Re–Os ages compared to the porphyry stock, ranging from 29.1 ± 0.2 to 28.1 ± 0.2 Ma (at 2σ level). The Siah Kamar porphyry Mo deposit is nearly temporally coeval with the Haft Cheshmeh porphyry Cu deposit and the vein-type Cu–Mo–Au mineralization in the Qarachilar area, corresponding to the second porphyry Cu–Mo mineralization epoch in NW Iran. However, it is younger than the majority of the porphyry Cu deposits in the southern Lesser Caucasus and only shows temporal correlation with the Paragachay and first-stage Kadjaran porphyry Cu deposits. Moreover, it is older than all the porphyry Cu–Mo systems across the central and south-eastern parts of the Urumieh–Dokhtar magmatic arc, except the Bondar Hanza deposit, which is nearly coeval with the Siah Kamar porphyry Mo deposit. All these data reveal an old to young trend along the UDMA and the porphyry Cu belt of Iran, further testifying to the diachronous and later closure of the Neo-Tethyan oceanic basin in central and SE Iran.